MAD(DENING) READING: JACEK GUTOROW, WALLACE STEVENS AND THE ANXIETY OF COMPARATIVE STUDIES - Pietrzak, Wit (Porównania, 2014)
In the present article I analyse Jacek Gutorow’s poem Nad brzegiem rzeki (At the River Bank) in relation to Wallace Stevens’s poetry. The methodological backbone for the essay is Harold Bloom’s theory of anxiety of influence. The struggle between an ephebe and a strong precursor are used in regard to the agon between the poet-translator and the poetry under translation. Translating Stevens’s works into Polish Gutorow creates a strong precursory presence in his native tongue with whom he as poet must now fight. It is in such a strife that Gutorow’s strongest vision is born, which links Stevens’s sublimity with rootedness in the familiar landscapes characteristic for Gutorow’s work.